'They do not care how much you know until they know how much you care': a qualitative meta-synthesis of patient experience in the emergency department. Issue 6 (19th April 2019) - Graham, Blair; Endacott, Ruth; Smith, Jason E; Latour, Jos M
Abstract : Background: Patient experience is positively associated with both clinical effectiveness and patient safety and should be a priority for emergency care providers. While both quantitative and qualitative approaches can be used to evaluate patient experience in the emergency department (ED), the latter is well aligned to develop a detailed understanding of features influencing the lived experience of ED patients. This study aimed to systematically review the literature of qualitative studies to identify determinants of adult patient experience in the ED. Methods: A Preferred Reporting Items for Systematic review and Meta-Analysis compliant systematic review was conducted using PubMed, CINAHL, EMBASE, BNI and bibliography searches to identify qualitative studies exploring patient experiences in ED published in English between 1997 and 2018. Quality assessment was conducted using the Critical Appraisal Skills Programme checklist. Descriptive text and quotations relating to patient experience were extracted from included studies and a meta-synthesis conducted using thematic analysis. Results: A total of 625 records were screened from which 40 studies underwent full review and 22 were included. Results were coded by two researchers (BG and JML). Meta-synthesis identified 198 discrete units of analysis which were clustered around five analytical themes. These were based on the perceived 'needs' of patients visiting the ED and were defined as communication, emotional, competent care, physical/environmental and waiting needs. Findings were translated into a conceptual model for optimising patient experience in the ED. Conclusion: This meta-synthesis provides a framework for understanding the determinants of patient experience in the ED. The resulting conceptual model and recommendations may have the potential to directly inform practice and improve the patient experience.